Molecular Characterization of Carbapenem-Resistant Acinetobacter baumannii Isolated from the Intensive Care Unit in a Tertiary Teaching Hospital in Malaysia - Jia Jie Woon; Cindy Shuan Ju Teh; Chun Wie Chong; Kartini Abdul Jabar; Sasheela Ponnampalavanar; Nuryana Idris (MDPI AG, 2021)
The emergence of carbapenem-resistant Acinetobacter baumannii (CRAB) has now become a global sentinel event. CRAB infections often instigate severe clinical complications and are potentially fatal, especially for debilitated patients. The present study aimed to conduct molecular characterization on CRAB isolated from patients in the intensive care unit from 2015 to 2016 and determine the risk factors associated with patients' mortality. One hundred CRAB isolates were retrospectively selected and included in this study. Antimicrobial susceptibility testing showed that all isolates remained susceptible to colistin, even though 62% of them conferred resistance to all other classes of antibiotics tested. OXA carbapenemase gene was found to be the predominant carbapenemase gene, with 99% of the isolates coharbouring blaOXA-23-like and blaOXA-51-like carbapenemase genes. All isolates were carrying intact CarO genes, with the presence of various degree of nucleotide insertion, deletion and substitution. Overall, PFGE subtyped the isolates into 13 distinct pulsotypes, with the presence of 2 predominant pulsotypes. Univariate analysis implied that age, infection/colonization by CRAB, ethnicity, comorbidity and CRAB specimen source were significantly associated with in-hospital mortality. Multivariate analysis identified a higher risk of mortality for patients who are of Chinese ethnicity with diabetes as an underlying disease. As CRAB infection could lead to high rate of mortality, comprehensive infection control measures are needed to minimize the spread of this pathogen.